Watch This: LOD -- Linking Open Data - Brooks, Terrence A (Information research, 2009)
The Web now contains many highly structured documents based on RDF (Resource Description Framework) architecture. Large pools of RDF documents, which are based on XML (Extensible Markup Language), can now be accessed in open Web space as part of the emerging "structured Web," also known as "data Web" or "linked data Web." According to the Linked Open Data (LOD) homepage, the linked data Web consists of two billion RDF documents as of October 2008. RDF architecture is a three-part structure that includes subject, predicate, and object. By linking among disparate data sets, it is possible to make discoveries by navigating from one document to another. Adapted from the source document.